2021
DOI: 10.3389/fendo.2021.635923
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between LXR and Caveolin-1 Signaling Supports Cholesterol Efflux and Anti-Inflammatory Pathways in Macrophages

Abstract: Macrophages are immune cells that play crucial roles in host defense against pathogens by triggering their exceptional phagocytic and inflammatory functions. Macrophages that reside in healthy tissues also accomplish important tasks to preserve organ homeostasis, including lipid uptake/efflux or apoptotic-cell clearance. Both homeostatic and inflammatory functions of macrophages require the precise stability of lipid-rich microdomains located at the cell membrane for the initiation of downstream signaling casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Additionally, miR-199a-5p is highly expressed in aorta and cardiometabolic tissues and organs such as aorta, heart, lung in humans, where hypoxia is a critical triggering factor of many associated diseases, including atherosclerosis. In this sense, besides the targeting key cholesterol genes ABCA1 or ABCG1 shown here, some of our recent studies demonstrated that Cav-1 may influence ABCA1 functions ( 57 ). Cav-1 is traditionally considered a cholesterol-binding protein that is able to shuttle cholesterol between various cell membranes ( 58 ), and acts as a central regulator of cholesterol metabolism during atherosclerosis, which varies depending on the cell type involved.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Additionally, miR-199a-5p is highly expressed in aorta and cardiometabolic tissues and organs such as aorta, heart, lung in humans, where hypoxia is a critical triggering factor of many associated diseases, including atherosclerosis. In this sense, besides the targeting key cholesterol genes ABCA1 or ABCG1 shown here, some of our recent studies demonstrated that Cav-1 may influence ABCA1 functions ( 57 ). Cav-1 is traditionally considered a cholesterol-binding protein that is able to shuttle cholesterol between various cell membranes ( 58 ), and acts as a central regulator of cholesterol metabolism during atherosclerosis, which varies depending on the cell type involved.…”
Section: Discussionmentioning
confidence: 60%
“…Cav-1 is traditionally considered a cholesterol-binding protein that is able to shuttle cholesterol between various cell membranes ( 58 ), and acts as a central regulator of cholesterol metabolism during atherosclerosis, which varies depending on the cell type involved. For instance, Cav-1 absence in aortic endothelial inhibits atherosclerosis by attenuating LDL transcytosis and enhancing autophagic flux ( 59 , 60 ), while in macrophages Cav-1 promotes THP-1 differentiation, ABCA1 expression and cholesterol efflux ( 57 , 61 , 62 ). Indeed, Cav-1 participates in LXR-dependent anti-atherogenic functions including ABCA1 localization, cholesterol efflux as well as the control of inflammatory responses in macrophages ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRs described herein are pivotal regulators of cellular catabolic metabolism in macrophages (see Table 1, where the known effects NRs specifically on cellular metabolism are listed). While PPARs regulate lipid and cholesterol metabolism, particularly in atherosclerosis, and were long recognised as modulators of myeloid cells and immunity, recent publications have revealed that also other NRs, previously only known to modulate immunity in macrophages through the regulation of cytokines and myeloid activation genes, can use cellular metabolism to achieve their immunoregulatory functions [70,92,113,121,122] (Table 1). Other transcription factors are intimately involved in cellular metabolism, the most prominent being HIF1a, which interacts with NRs, and is a major node in the control of myeloid metabolism by NR.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the complicated roles of fatty acid β-oxidation in IL-4-driven M2 macrophage differentiation, unsaturated fatty acids such as oleate promote the immunosuppressive and pro-tumor phenotype of TAMs through lipid droplet-dependent mechanisms 83 . In addition, SREBP1-dependent production of anti-inflammatory fatty acids contributes to the resolution of TLR4-mediated inflammation 84 , and Caveolin-1 participates in LXR-dependent cholesterol efflux and mediates anti-inflammatory properties 85 . Similarly, ovarian cancer cells facilitate membrane cholesterol efflux in TAMs, thus resulting in lipid raft breakdown and a subsequent increase in IL-4 signaling, which fosters the immunosuppressive TAM phenotype 86 .…”
Section: Lipid Metabolism Regulates Immune Responses To Tumorsmentioning
confidence: 99%